2021
DOI: 10.1177/2059513120988532
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical treatment of ex vivo human abdominal skin and potential use in scar management: A pilot study

Abstract: Introduction: Scar treatments aim to address pathologic collagen deposition; however, they can be expensive or difficult to control. Electrochemical therapy (ECT) offers a simple alternative treatment. The purpose of this study is to examine the acid-base and histological changes in ex vivo human abdominal skin following ECT. Methods: Forty-two ex vivo human panniculus tissue sections collected from six individuals were tumesced with normal saline. ECT was performed by inserting two platinum needle electrodes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…This was the highest dosimetry parameter tested for P‐ECLL and may represent an upper limit dosimetry limit. Hyperpigmentation of the skin at the needle insertion and exit points was also observed here as in previous studies 31,34,35 . This is a common effect observed in many energy‐based skin therapies and is an unpredictable process associated with moderate tissue injury 40–43 .…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…This was the highest dosimetry parameter tested for P‐ECLL and may represent an upper limit dosimetry limit. Hyperpigmentation of the skin at the needle insertion and exit points was also observed here as in previous studies 31,34,35 . This is a common effect observed in many energy‐based skin therapies and is an unpredictable process associated with moderate tissue injury 40–43 .…”
Section: Discussionsupporting
confidence: 85%
“…Hyperpigmentation of the skin at the needle insertion and exit points was also observed here as in previous studies. 31,34,35 This is a common effect observed in many energy-based skin therapies and is an unpredictable process associated with moderate tissue injury. [40][41][42][43] This needs to be further explored if this technology is to be directed for treating skin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Volume 153, Number 2 • In Vivo Electrochemical Lipolysis 335e new, low-cost, nonsurgical fat reduction modality involving the use of in situ water hydrolysis to modify the biochemical and physical tissue properties. We have demonstrated that in situ water electrolysis to generate acid (at the anode) and base (at the cathode) can modify cartilage pliability, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] cause localized collagen injury to skin, [33][34][35][36][37] and induce adipocyte necrosis and lipolysis when applied to fat. 38,39 In this latter application, referred to as electrochemical lipolysis (ECLL), saline is first injected into fat for tumescence and to increase tissue electrical conductivity.…”
mentioning
confidence: 99%